High consumption of sucrose induces DNA damage in male Wistar rats - FRANKE,SILVIA I.R. (2017)
ABSTRACT The purpose of this study was to determine the effects of the high consumption of sucrose on the levels of DNA damage in blood, hippocampus and bone marrow of rats. Male Wistar rats were treated for 4 months with sucrose (10% for 60 initial days and 34% for the following 60 days) in drinking water, and then, glycemia and glycated hemoglobin (A1C) were measured. Levels of DNA damage in blood and hippocampus were evaluated by the comet assay. The micronucleus test was used to evaluate chromosomal damages in the bone marrow. The sucrose treatment significantly increased (p<0.01) the serum glucose levels (~20%) and A1C (~60%). The level of primary DNA damage was significantly increased (p<0.05) in hippocampal cells (~60%) but not in peripheral blood leukocytes (p>0.05). Additionally, it was observed a significative increase (p<0.05) in the markers of chromosomal breaks/losses in bone marrow, as indicated by the micronucleus test. This is the first study that evaluated DNA damage induced by high sucrose concentration in the hippocampus and bone marrow of rats. Sucrose-induced DNA damage was observed in both tissues. However, the mechanism of sucrose toxicity on DNA remains unknown.